Arterial stiffness and wave reflection: Biomarkers of cardiovascular risk - Mitchell, Gary F. (Artery research, 2009)
Arterial stiffness and excessive pressure pulsatility have emerged as important risk factors for cardiovascular disease. Arterial stiffness increases with age and in the presence of traditional cardiovascular disease risk factors, such as hypertension, diabetes and lipid disorders. Pathologic stiffening of large arteries with advancing age and risk factor exposure predominantly involves the elastic aorta and carotid arteries, whereas stiffness changes are relatively limited in muscular arteries. Aortic stiffening is associated with increased pulse wave velocity and pulse pressure, which are related but distinct measures of the pulsatile energy content of the pressure waveform. A dramatic increase in pulsatile energy content of pressure and flow waves in the arterial system places considerable pulsatile stress on the heart, large arteries and distal circulation. Large artery stiffening is associated with abnormalities in microvascular structure and function that may contribute to tissue damage, particularly in susceptible high flow organs such as the brain and kidneys. This brief review summarizes results of recent research on risk factors for and adverse effects of large artery stiffening.